FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2010-2013 - Yuni Andriany; Rita Anugerah; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research is to investigate the factors that effect audit delay and timeliness of financial reporting by banking companies listed on the Indonesia Stock Exchange from 2010 to 2013. Samples are 120 companies selected by using purposive sampling method. Multiple linear regression analysis is used to investigate influenced audit delay factors, and logistic regression analysis is used to investigate influenced timeliness factors. These results show that company age with significant 0,035, auditor’s opinion with signifact 0,000, and audit firm size with significant 0,009 have effect on audit delay. However, profitability and solvability have no significant effect on audit delay. Furthermore, auditor’s opinion with significant 0,000 and audit firm size with significant 0,031 also have effect on timeliness of publication financial reports. But, company age, profitability and solvability have no significant effect on timeliness of publication financial reports.Keywords: audit delay, timeliness, purposive sampling, multiple linear regression, and logistic regression.